1978
DOI: 10.1139/b78-347
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanin pigmentation in roots of Impatiens species

Abstract: A red anthocyanin pigmentation has been investigated in root tips and mature roots of seedlings and potted plants of Impatiens (Balsaminaceae): I. balfourii, I. balsamina, I. capensis, I. flaccida, I. linearifolia, I. platypetala, I. repens, I. schlechteri, I. sultani, I. uguenensis, and several hybrid cultivars. Reddening of root tips when present in young seedlings occurs also in mature plants and seems to be a continuing feature of root development. The appearance of red pigmentation in mature root tissues … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1979
1979
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Anthocyanins are located predominantly in the epidermal, hypodermal, and superficial cortical layers of adventitious roots in M. excelsa. Similar histological distributions have been observed in some Impatiens species (Thakur & Nozzolillo 1978). Our results also highlight variability in the distribution Pattern of anthocyanins among mature root tissues.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Anthocyanins are located predominantly in the epidermal, hypodermal, and superficial cortical layers of adventitious roots in M. excelsa. Similar histological distributions have been observed in some Impatiens species (Thakur & Nozzolillo 1978). Our results also highlight variability in the distribution Pattern of anthocyanins among mature root tissues.…”
Section: Discussionsupporting
confidence: 87%
“…By contrast, the flowers of M. excelsa contain up to 11 anthocyanins based on Cy, Dp, Mv, Pn, and Pt (Cambie & Seelye 1961;Anderson 1988). Cy has been found also in roots of Impatiens species (Thakur & Nozzolillo 1978), and Cy and Pg were reported to be present in the roots of different varieties of Raphanus sativus (Harborne 1963;Ishikura & Hayashi 1962, 1963. The glycoside components of root anthocyanins in M. excelsa require identification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the roots of Metrosideros excelsa exposed to light cyanidin and delphinidin were found (Solangaarachchi and Gould, 2001). Cyanidin was also identified in the roots of Impatiens (Thakur and Nozzolillo, 1978) and the presence of cyanidin and pelargonidin was recorded in the roots of Raphanus sativus (Harborne, 1963;Ishikura and Hayashi, 1962). Cyanidin is the most common among plants.…”
Section: Discussionmentioning
confidence: 96%
“…Accumulation of anthocyanin in roots exposed to daylight has been observed in Salix and Zea (Tselas et al, 1979), Fragaria × ananasa (Nemec, 1973), Impatiens spp. (Thakur and Nozzolillo, 1978) and in Metrosideros excelsa (Solangaarachchi and Gould, 2001). Shimizu et al (2010) reported that light irradiation was essential for anthocyanin accumulation induced by JA-Me treatment in Gynura bicolor cultured roots.…”
Section: Discussionmentioning
confidence: 99%